2006
DOI: 10.1002/yea.1353
|View full text |Cite
|
Sign up to set email alerts
|

The budding yeast rRNA and ribosome biosynthesis (RRB) regulon contains over 200 genes

Abstract: The ribosome biogenesis pathway constitutes one of the major metabolic obligations for a dividing yeast cell and it depends upon the activity of hundreds of gene products to produce the necessary rRNA and ribosomal protein components. Previously, we reported that a set of 65 S. cerevisiae genes that function in the rRNA biosynthesis pathway are transcriptionally co-regulated as cells pass through a variety of physiological transitions. By analysing multiple microarray-based transcriptional datasets, we have ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
133
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(149 citation statements)
references
References 29 publications
13
133
0
1
Order By: Relevance
“…The promoters of Ribi genes are highly enriched in PAC motifs (7,12,13). The Saccharomyces Genome Database currently annotates 303 nonribosomal protein genes in the functional category of ribosome biogenesis, and 199 of these overlap with the 647 genes whose promoters contain one or more PAC sites (P Ͻ 10 Ϫ190 ).…”
Section: Repression Of Ribi Genes In Response To Torc1 Inactivation Rmentioning
confidence: 99%
See 2 more Smart Citations
“…The promoters of Ribi genes are highly enriched in PAC motifs (7,12,13). The Saccharomyces Genome Database currently annotates 303 nonribosomal protein genes in the functional category of ribosome biogenesis, and 199 of these overlap with the 647 genes whose promoters contain one or more PAC sites (P Ͻ 10 Ϫ190 ).…”
Section: Repression Of Ribi Genes In Response To Torc1 Inactivation Rmentioning
confidence: 99%
“…Moreover, another Ϸ300 genes encoding nonribosomal proteins are involved in various aspects of ribosome assembly and translational capacity (the ribosome biogenesis, or Ribi, regulon): RNA polymerases I and III subunits, tRNA synthetases, rRNA processing and modifying enzymes, translation factors, etc. (6,7). Synthesis of the translation machinery is very energetically expensive to the cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Promoters of the glucose-induced ribosomal biogenesis genes are highly enriched for RRPE and PAC motifs (Beer and Tavazoie, 2004;Jorgensen et al, 2004;Wade et al, 2006). Quite strikingly, in the promoters of those genes containing a PAC or RRPE motif (labeled Motif B in Figure 6) that were subsequently induced by glucose addition, the motifs were significantly more exposed than they were in those genes that were subsequently repressed or remained unchanged upon glucose addition, suggesting that likely physiologically relevant occurrences of RRPE/PAC motifs may be free of nucleosomes and accessible, whereas likely spurious instances of the RRPE/PAC motifs in promoters of repressed or unchanged genes are more likely to be contained within nucleosomes and perhaps inaccessible.…”
Section: Functional Transcription Factor Binding Motifs Reside In Regmentioning
confidence: 99%
“…We found that the promoters of the RRB genes were enriched for the PAC and RRPE promoter motifs, and substitutions in these motifs disturbed the regulated expression of candidate RRB genes in vivo [5]. By analyzing genome-wide expression profiles, and cross referencing with the presence of the conserved promoter motifs, we were able to suggest that the RRB regulon contained some 200 members, even though many of the genes had at the time, no ascribed function [5,6].These predictions have turned out to be fairly accurate, as since then some 90% of the unknown members have been subsequently identified as contributing towards ribosome and rRNA biogenesis. The factors that recognize the PAC and RRPE motifs have also been subsequently identified (the Stb3 and Tod6/Dot6 proteins respectively), and they have been shown to play key roles in RRB gene regulation [7].…”
mentioning
confidence: 90%